End-Expiratory Occlusion Test Predicts Fluid Responsiveness in Patients With Protective Ventilation in the Operating Room. (December 2017) - Biais, Matthieu; Larghi, Mathilde; Henriot, Jeremy; de Courson, Hugues; Sesay, Musa; Nouette-Gaulain, Karine
Abstract : BACKGROUND: End-expiratory occlusion test (EEOT) has been proposed to predict fluid responsiveness in mechanically ventilated intensive care unit patients. The utility of this test during low-tidal-volume ventilation remains uncertain. This study aimed to determine whether hemodynamic variations induced by EEOT could predict the effect of volume expansion in patients with protective ventilation in the operating room. METHODS: Forty-one patients undergoing neurosurgery were included. Stroke volume and pulse pressure variations were continuously recorded using pulse contour analysis before and immediately after a 30-second EEOT and after volume expansion (250 mL saline 0.9% given over 10 minutes). Patients with an increase in stroke volume ≥ 10% after volume expansion were defined as responders. RESULTS: Twenty patients were responders to fluid administration. EEOT induced a significant increase in stroke volume, which was correlated with the stroke volume changes induced by volume expansion (r 2 = 0.55, P < .0001). A 5% increase in stroke volume during EEOT discriminated responders to volume expansion with a sensitivity of 100% (95% confidence interval [CI], 83%–100%), a specificity of 81% (95% CI, 58%–95%), a positive predictive value of 84% (95% CI, 64%–96%), and a negative predictive value of 100% (95% CI, 80%–100%). The gray zone ranged from 4% to 8%, including 17% of patients. The best pulse pressure variation threshold was 9%, with a sensitivity of 60% (95% CI, 36%–81%) and specificity of 86% (95% CI, 64%–97%). The area under the receiver operating characteristics curve generated for changes in stroke volume induced by EEOT (0.91, 95% CI, 0.81–1.00) was significantly higher than the one obtained for pulse pressure variations (0.75, 95% CI, 0.60–0.90); P < .05. CONCLUSIONS: Changes in stroke volume index induced by EEOT can predict fluid responsiveness in patients with protective ventilation in the operating room. This test may have potential applications. Abstract : Published ahead of print July 21, 2017.